Communicating with parents who have difficulty understanding and speaking Swedish: An interview study with health care professionals. Issue 6 (December 2017) - Patriksson, Katarina; Berg, Marie; Nilsson, Stefan; Wigert, Helena
Abstract: Background: Neonatal units care for sick and premature newborns, and staff meet the children's parents on a daily basis. Some parents are immigrants and do not speak or understand the local language, hampering both verbal communication and the parents' opportunity to be involved in their child's care and treatment. Aim: To explore the experiences of health care professionals in Swedish neonatal care units regarding communication with parents of foreign origin who have difficulty understanding and speaking Swedish. Methods: Individual open-ended interviews were conducted with 60 health care professionals at five neonatal care units in western Sweden: 10 physicians, 25 nurses, and 25 nursing assistants. The interviews were analysed using qualitative content analysis. Results: The health care professionals' experiences were summarised in one main category: "Powerlessness in the face of inadequate care routines leading to failure to communicate." The main category was constructed through three categories. " Inability to perform their work properly " meant that staff experienced frustration when they could not convey important information to parents. " Finding their own strategies " meant that staff found their own ways to communicate using body language and assistive technology. " Dependence on others " meant that staff were dependent on others, primarily talking through an interpreter. Conclusion: There is a need for organizational changes to increase parents' participation in their child's care in daily practice at neonatal care units. To ensure that parents who do not speak or understand the Swedish language are given sufficient time and possibilities, routines must be established in which interpreters are used more frequently.